2021
DOI: 10.1049/sil2.12030
|View full text |Cite
|
Sign up to set email alerts
|

Hammerstein system with a stochastic input of arbitrary/unknown autocorrelation – nonparametric estimator of the static nonlinear subsystem

Abstract: This study proposes the first estimator in the open literature (to the present authors' best knowledge) to nonparametrically estimate a Hammerstein system's nonlinear static subsystem when excited by an input that is temporally self-correlated with an unknown spectrum, an unknown variance and an unknown mean (instead of the input as commonly presumed to be white and zero-mean). This proposed nonparametric estimator is analytically proved here to be asymptotically unbiased and pointwise consistent. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(230 reference statements)
0
1
0
Order By: Relevance
“…For the Hammerstein system's other constituent subsystem (i.e. the non-linear static subsystem), a non-parametric estimator has been developed in a companion study [77] for a similar signal/noise statistics model as indicated herein. These two subsystems' estimators are algorithmically independent from each other, in the sense that each may be computed without computing the other, or that the two may be computed simultaneously in parallel.…”
Section: F G U R Ementioning
confidence: 99%
“…For the Hammerstein system's other constituent subsystem (i.e. the non-linear static subsystem), a non-parametric estimator has been developed in a companion study [77] for a similar signal/noise statistics model as indicated herein. These two subsystems' estimators are algorithmically independent from each other, in the sense that each may be computed without computing the other, or that the two may be computed simultaneously in parallel.…”
Section: F G U R Ementioning
confidence: 99%